10‐valent pneumococcal non‐typeable Haemophilus influenzae protein‐D conjugate vaccine (PHiD‐CV) induces memory B cell responses in healthy Kenyan toddlers. (10th June 2015) - Muema, D. M.; Nduati, E. W.; Uyoga, M.; Bashraheil, M.; Scott, J. A. G.; Hammitt, L. L.; Urban, B. C.
Summary Memory B cells are long‐lived and could contribute to persistence of humoral immunity by maintaining the plasma‐cell pool or making recall responses upon re‐exposure to an antigen. We determined the ability of a pneumococcal conjugate vaccine to induce anti‐pneumococcal memory B cells. Frequencies of memory B cells against pneumococcal capsular polysaccharides from serotypes 1, 6B, 14, 19F and 23F were determined by cultured B cell enzyme‐linked immunospot (ELISPOT) in 35 children aged 12–23 months who received pneumococcal non‐typeable Haemophilus influenzae protein‐D conjugate vaccine (PHiD‐CV). The relationships between plasma antibodies and memory B cell frequencies were also assessed. After two doses of PHiD‐CV, the proportion of subjects with detectable memory B cells against pneumococcal capsular polysaccharides increased significantly for serotypes 1 (3–45%; P < 0·01), 19F (21–66%; P < 0·01) and 23F (13–36%; P = 0·02), but not serotypes 6B (24–42%; P = 0·24) and 14 (21–40%; P = 0·06). Correlations between antibodies and memory B cells were weak. Carriage of serotype 19F at enrolment was associated with poor memory B cell responses against this serotype at subsequent time‐points (day 30: non‐carriers, 82% versus carriers, 0%, P < 0·01; day 210: non‐carriers, 72% versus carriers, 33%, P = 0·07). PHiD‐CV is capable of inducing memory B cells against some of the component pneumococcal capsular polysaccharides.